Histochemical properties of sialic acids and antimicrobial substances in canine anal glands - Nara, T. (PAGEPress Publications, 2011)
The functional properties of sialic acids appear to be manifold. Additionally, antimicrobial substances serve as a non-specific defense against microorganisms. In this study, therefore, the localization of sialic acids and antimicrobial substances in the anal glands of dog was studied by sialoglycoconjugate histochemistry and immunohistochemistry. The secretory epithelium, luminal secretions and excretory ducts exhibited high levels of sialoglycoconjugates that terminated in Siaα2-6Gal/GalNAc or Siaα2-3Gal1-4GlcNAc. Additionally, O-acetylated sialic acids were detectable in these glandular structures. Antimicrobial substances, such as lysozyme, immunoglobulin A (IgA), lactoferrin and the peptide group of β-defensins, were also demonstrated as products of the anal glands. The results obtained are discussed with regard to the functional significance of the anal glands. These secretory products may create a defensive barrier against microbial invasion at the anal mucosa.